PENERAPAN AKUNTANSI PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) - Kurniawati, Elisabeth Penti; Nugroho, Paskah Ika; Arifin, Chandra (Jurnal Manajemen dan Keuangan, 2012)
Accounting is an information system that produces a report for the stakeholders about the economic activities and condition of the company. Micro, Small and Medium Enterprises (MSMEs) as nations economy cantilever, a lot of these company have not been applied accounting in their business. The objective of this research is to identify and analyze the application and the obstacle of accounting at the Micro, Small and Medium Enterprises (MSMEs). The research took 51 MSMEs in Salatiga using convenience sampling method. The data used are primary data obtained through interviews and questionnaires. Techniques analysis of this research is a qualitative descriptive analysis techniques. Results showed that most SMEs in Salatiga already keep records of sales, purchasing, inventory, payroll expenses and other costs. While reporting statements made include sales, purchasing, inventory and payroll. Obstacles that hinder SMEs in the application of accounting include educational background, have not been trained accounting and havenât need with accounting application.Keywords: Accounting, Micro, Small and Medium Enterprises (MSMEs)